STRATEGI IMPLEMENTASI PENDIDIKAN QUR'ANI - Rosnidarwati Rosnidarwati; Restu Andrian (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2019)
The education in the Islamic studies is the discussion period about at-tarbiyah, al-ta'lÄ«m and al-ta'dÄ«b. The term are popularly used in Islamic education is at-tarbiyah. The creation of Qur'ani education goals is a great effort for humans to prepare the provisions of the life of the world and the hereafter while completing physical and spiritual balance as a complete container for oneself. The personality that is the target of Islamic education is